КЕЎИЛ АЙТЫЎ (И.Юсуповтың «Кеўил айтыў» (Яхыт жеңгей қайтыс болғанда Жолмурза ағаға айтылған сөз дөретпеси мысалында) - Бауатдинова, С. (FAN va JAMIYAT, 2020)
The author of the article describes the features and peculiarities of the "condolences" genre in the Karakalpak folklore. The work "Condolences" created by the poet I. Yusupov in a new literary form is being interpreted. The importance of the "condolence" genre and its connection with people's lives is widely discussed.